REFLECTION BUILT ON LANGUAGING AS AN ALTERNATIVE TO FEEDBACK: DEVELOPING PROCEDURAL LANGUAGE AWARENESS OF THE CONSTRUCTIONIST NATURE OF KNOWLEDGE AND LANGUAGE AMONG PROSPECTIVE L2 LANGUAGE TEACHERS - Lankiewicz, Hadrian (Neofilolog, 2019)
While teacher feedback has got a long established tradition in pedagogic or educational discourse as a form of reflection, it has to be noticed by students to result in raised awareness. Apprehension of teacher feedback depends on its various characteristics such as salience, length, complexity or linguistic features (Swain, 2006a). Thereby its value may be too much engrained in the positivist paradigm of knowledge and language. Sociocultural approaches to learning, resting firmly on constructivist theories of knowledge and interactive theories of language, underscore the centrality of the learner. The agency of the learner places reflection in the form of talks (Moate, 2011) or languaging (Swan, 2006a). The aim of this paper is to present a microgenetic analysis of languaging on the concept of “noticing” (Schmidt, 1990) in teacher training during a methodology class. The working hypothesis is the claim that reflection, in the form of substantiated thinking, presents a potential for developing procedural dimension of teacher language awareness.